A relação entre orientação para o mercado, desempenhoorganizacional e a percepção externa de sucesso ou insucessocorporativo: uma análise sobre as instituições de pesquisas tecnológicasbrasileiras - Newton Amaral Paim (2010)
Market orientation has attracted significant investigative and editorial interest in recent decades and occupied a central position in the theory and practice of marketing strategy. Although the literature features a variety of empirical studies on market orientation, a review of it suggests that the majority of these studies have focused on industrialized countries and companies engaged in manufacturing activities and services supplying. Empirical research in the market orientation field focused on the type of organization that does not necessarily pursue profit remains limited, both in developed countries and emerging markets, particularly Brazil, despite the occurrence of positive modifications and transformations in the business environment in developing economies such as ours. In an attempt to examine the importance of market orientation, this study investigated its relationship with organizational performance and external perceptions of success or failure in Brazilian technological research institutions core activities. Univariate and multivariate statistical techniques were used to validate constructs concerning measurement methods employed, obtain high levels of adjustment to the theoretical structure proposed, and confirm all four hypotheses and the three researchderived hypotheses tested. The results of the research showed that market orientation in technological research institutions in Brazil has a positive and significant relationship with the organizational performance of these institutions, and this association is clearly visible to a group of experts in the Brazilian science and technology field who are external to these institutions, in assessing how successful or unsuccessful these institutions are in carrying out their core activities.